Pedetan Ethnochemistry Typical of Jembrana and it’s Integration into Green Chemistry Learning - Savitri, Ni Komang Ananda Dian; Suja, I Wayan; Maryam, Siti (Hydrogen: Jurnal Kependidikan Kimia, 2026)
This study aims to explore the ethnochemical knowledge embedded in the traditional production of Jembrana’s pedetan and to analyze its potential integration into high school green chemistry learning. This research is motivated by the limited ethnochemical studies that highlight local Balinese culinary, especially pedetan, and the absence of studies that specifically link the pedetan production process with the principles of green chemistry as a source of contextual learning. The study uses a qualitative approach with an ethnographic type. The research subjects involved pedetan cooks in Perancak Village, as well as literature sources in the form of books, scientific journals, and the chemistry syllabus of the Merdeka Curriculum. The research objects include local knowledge related to the ingredients and process of making pedetan along with the accompanying chemical phenomena, a study of the chemical content of the ingredients and their benefits, and their suitability with the learning outcomes of high school chemistry. Data collection was conducted through direct observation of the production process, in-depth interviews with informants, and documentation in the form of photographs, field notes, and supporting documents. Data validity was tested through triangulation, reference adequacy, and member checking to ensure consistency with information from informants. The results of the study showed that the main ingredients of pedetan consisted of three types of fish, namely lemuru ( Sardinella lemuru ), tambang ( Sardinella fimbriata ), and layang ( Decapterus ), as well as seven types of plant spices, namely turmeric ( Curcuma longa ), red chili ( Capsicum annuum L. ), galangal ( Alpinia galanga ), coriander ( Coriandrum sativum L. ) , garlic ( Allium sativum L. ), lemongrass ( Cymbopogon citratus ), and aromatic ginger ( Kaempferia galanga L. ). The manufacturing process includes fish cutting, washing, soaking, seasoning, and drying, each of which involves various chemical phenomena. These findings have the potential to be integrated into high school chemistry education, particularly in green chemistry content, through green chemistry principles that align with the pedetan production process. This study recommends the development of broader ethnochemical studies, strengthening through experimental testing, and its use by teachers to support more meaningful contextual learning.